The Empire of Love Toward a Theory of Intimacy, Genealogy, and Carnality - Povinelli, Elizabeth A. (Public planet books, 2006)
In The Empire of Love anthropologist Elizabeth A. Povinelli reflects on a set of ethical and normative claims about the governance of love, sociality, and the body that circulates in liberal settler colonies such as the United States and Australia. She boldly theorizes intimate relations as pivotal sites where liberal logics and aspirations absorbed through settler imperialism are manifest, where discourses of self-sovereignty, social constraint, and value converge.For more than twenty years, Povinelli has traveled to the social worlds of indigenous men and women living at Belyuen, a small community in the Northern Territory of Australia. More recently she has moved across communities of alternative progressive queer movements in the United States, particularly those who identify as radical faeries. In this book she traces how liberal binary concepts of individual freedom and social constraint influence understandings of intimacy in these two worlds. At the same time, she describes alternative models of social relations within each group in order to highlight modes of intimacy that transcend a reductive choice between freedom and constraint.Shifting focus away from identities toward the social matrices out of which identities and divisions emerge, Povinelli offers a framework for thinking through such issues as what counts as sexuality and which forms of intimate social relations result in the distribution of rights, recognition, and resources, and which do not. In The Empire of Love Povinelli calls for, and begins to formulate, a politics of "thick life," a way of representing social life nuanced enough to meet the density and variation of actual social worlds